Researchizs on biochemical, antibiotics sensitivity and transferable drug - resistance ( r - factor) characteristics of e. c ali strains isolated from diarrheal calves in konya region. - Mehmet ATEŞ; İ. Yavuz SEZEN; Osman ERGANİŞ; Mehmet ÇORLU (Eurasian Journal of Veterinary Sciences)
In this study, same biochemical characteristics, different antibiotics resistance states and R- factor transmissibility of 51 E. coli strain.s isolated from calves with diarrhea up to one week age were examined. Biochemical characteristics of the strains were found to be as follows: The rates for glucose, lactose, mannitol dulsitol, arabinose and adonitol fermentation tests were 100 %, 100%, 100 %, 54.9 %, 98.1 % and 21.6 % respectively and the rates for urease production, citrate utilization, tryp- tophane deaminase, H2S, indol and .motility tests were 100 %, 0.0 %, 0.0 %, 0.0 %, 100%, 0.0 %, 96.1% and 80.4% respectively. It was observed that only one of the whore strains ( 1.96 %) passessed a hemolytic activity. According to the results of disk diffusion method, antiıbiotic resistance rates of E. coli strains were determined as follows 70.5 % for tetracyline, 86.2 % for oxytetracycline and neomisin, 98.1 % for erytromisin, 54.9% for ampisilin, 49.0 % for streptomisin, 23.4 % for chloramphenicole and 5.9% for nalidixic acide. Of the strains 94.1 per cent were resistant to more than 3 antibiotics. The rates of R – plasmid transmission of the strain were found to be 27.1 per cent.